Evaluation of Radioactivity in Soil Sample from Al-Hadbaa Cement Plant in Nineveh Governorate, Iraq - Yaseen, Ali I.; Najam, Laith A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
The fundamental goal of this study is to measure the level of radioactivity in the soil of the area around Al-Hadbaa cement plant, also to evaluate the radiological hazard of radionuclide, gamma-spectroscopy with an HPGe detector with the crystal diameter of 70.6 mm and length of 70 mm has been used to estimate the specific activity of natural radionuclides 226Ra, 232Th, 40K, and artificial radionuclides 137Cs in the fifteen soil samples collected. The results show that the average concentration of specific activity of 226Ra, 232Th, 40K, and 137Cs was 11.17 ± 1.69, 13.38 ± 0.72, 158.36 ± 5.35 Bq/kg, and 1.52 ± 0.19 Bq/kg, respectively. The average specific activity of these radionuclides is discovered to be lower than the global average which is 33 Bq/kg for 226Ra, 30 Bq/kg for 232Th, and 400 Bq/kg for 40K. Radiological hazard indices are determined according to the activity concentration of the radionuclides in the area under study. The outcome of the radiological hazard index is within the globally recognized limit proposed by UNSCEAR which is 1000 μSv/y for annual effective dose and 290 × 10-6 for cancer risk, so it is possible to conclude that there are no radiological hazards as a result of radiation exposure to the workers working in the cement plant as well as the organisms living in the region.